1991
DOI: 10.1002/cjce.5450690326
|View full text |Cite
|
Sign up to set email alerts
|

CO2 gasification kinetics of two alberta coal chars

Abstract: 10, gasification kinetics of chars from two Alberta coals (Obed Mountain, high volatile bituminous and Highvale, subbituminous) have been studied using a thermogravimetric analyzer (TGA) and a fixed bed reactor. Charification and gasification reactions were performed sequentially in both the TGA instrument and in the fixed bed reactor to simulate real gasifier operating conditions. TGA and fixed bed data were processed numerically to evaluate the kinetic rate of CO, gasification of the chars. Calculated gasifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
2
14
0
2
Order By: Relevance
“…As expected, higher gasification rates are noticed with smaller particles, the main features like diffusion restrictions and heat transfer limitations cannot be ignored while considering the high ash coal, over the temperature and sizes of coals tested [35]. As noted earlier [48,[54][55][56][57], the reduction in coal particle size, the TG and the DTG curves move into lower temperature regions, and burning rate increment of coal is seen so time for burnout is reduced. Owing to the fact that the more specific area available with the smaller pulverized coal particles influences the gasification rate over the larger ones, also smaller particles are favorable to the development and ignition of the coal particles.…”
Section: Effect Of Particle Size On Co 2 Gasificationsupporting
confidence: 59%
“…As expected, higher gasification rates are noticed with smaller particles, the main features like diffusion restrictions and heat transfer limitations cannot be ignored while considering the high ash coal, over the temperature and sizes of coals tested [35]. As noted earlier [48,[54][55][56][57], the reduction in coal particle size, the TG and the DTG curves move into lower temperature regions, and burning rate increment of coal is seen so time for burnout is reduced. Owing to the fact that the more specific area available with the smaller pulverized coal particles influences the gasification rate over the larger ones, also smaller particles are favorable to the development and ignition of the coal particles.…”
Section: Effect Of Particle Size On Co 2 Gasificationsupporting
confidence: 59%
“…Some other researchers found a linear decrease of gasification rate as reaction advances [26,27]. However, some studies regarding coal reactivity during gasification do not consider gasification rate variation with conversion and only report rate of gasification at a specific value of conversion [28,29]. Fig.…”
Section: Effect Of Coal Rankmentioning
confidence: 98%
“…Kovacik et al [28] found diffusion restrictions for sub-bituminous and bituminous coals at 900 C and different particle size ranges i.e. À105 þ 74 mm (À140 þ 200 mesh), À600 þ 350 mm (À30 þ 45 mesh), and À2.4 þ 1.7 mm (À7 þ 14 mesh).…”
Section: Particle Sizementioning
confidence: 99%
“…By using the Arrhenius equation, the following expression can be derived [10][11][12][13][14][15][16][17][18][19]:…”
Section: Solid Phase Analysismentioning
confidence: 99%